PAINLESS EXTRACTION IN CLEFT LIP AND PALATE PATIENTS USING COMPUTER-CONTROLLED LOCAL ANESTHETIC DELIVERY (CCLAD) FOR MAXILLARY NERVE BLOCKS - Maria Andisa Mayangsari; Inne Suherna Sasmita; Hilmanda (Fakultas Kedokteran Gigi Unjani, 2026)
Dental treatment in pediatric patients with cleft lip and palate (CLP) presents unique challenges due to anatomical variations, altered innervation, scar tissue formation, and increased tissue sensitivity in the cleft area. Achieving effective and comfortable local anesthesia is essential, particularly when performing procedures adjacent to the cleft. A 5-year-old male patient diagnosed with unilateral left cleft lip and palate presented with pulp necrosis of tooth 62 due to deep caries. The tooth was located directly adjacent to the palatal cleft. The patient was categorized as high caries risk and demonstrated positive behavior (Frankl 3). Extraction of tooth 62 was indicated to eliminate focal infection. Local anesthesia was administered using a CCLAD system (The Wand®). Anesthetic management included topical anesthesia, Anterior Middle Superior Alveolar (AMSA) nerve block, Palatal Approach–Anterior Superior Alveolar (P-ASA) nerve block, and supplemental local infiltration with slow anesthetic deposition. Clinical signs confirmed adequate anesthesia prior to extraction. The procedure was completed successfully without intraoperative or postoperative complications. Follow-up examination revealed satisfactory healing. Careful consideration of anatomical and neurovascular variations in CLP patients is essential for successful anesthetic management. The use of CCLAD, combined with appropriate nerve block techniques and controlled anesthetic delivery, can enhance patient comfort and procedural effectiveness in pediatric cleft patients undergoing tooth extraction. DOI : 10.54052/jhds.v6n1.p65-78